Challenges on the Emmaus Road : Episcopal bishops confront slavery, Civil War, and emancipation - Dorn, T. Felder (The University of South Carolina Press, 2013)
"Focuses on the way Northern and Southern Episcopal bishops confronted and responded to the issues and events of their turbulent times ... Dorn devotes the final chapters to the postwar reunification of the Episcopal Church and Southern bishops' involvement in establishing the Commission on Freedmen to offer help with the educational and spiritual needs of the recently emancipated slaves"--Jacket